Experimental analysis of harmonic distortions in the excitation currents of double-excited three-phase transformers - Rossi, J. C.; de Oliveira, L C O (Institute of Electrical and Electronics Engineers (IEEE), 2000)
This paper shows the results of experimental investigations of three-phase banks composed of single-phase transformers and three-phase three-limb core transformers under simultaneous alternating and direct current excitations, for several winding connections. Harmonic analysis of excitation currents for different de saturation levels is performed.
Keywords: asymmetrical magnetization; transformers